2023
DOI: 10.1001/jamasurg.2022.6998
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Esophageal and Gastric Cancer After Bariatric Surgery

Abstract: ImportanceBariatric surgery has been associated with a reduced risk of cancer in individuals with obesity. The association of bariatric surgery with esophageal and gastric cancer is still controversial, however.ObjectiveTo compare the incidence of esophageal and gastric cancer between patients with obesity who underwent bariatric surgery and those who did not (control group).Design, Setting, and ParticipantsThis cohort study obtained data from a national discharge database, including all surgical centers, in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Nonetheless, the results reported by Lazzati et al give both patients and clinicians further reassurance of the protective clinical benefits of weight loss surgery. More large-scale studies are needed to focus on the clinical paradox of esophagogastric protection for operations that may increase GERD.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, the results reported by Lazzati et al give both patients and clinicians further reassurance of the protective clinical benefits of weight loss surgery. More large-scale studies are needed to focus on the clinical paradox of esophagogastric protection for operations that may increase GERD.…”
mentioning
confidence: 93%
“…Some potential protective mechanisms for cancer reduction in addition to surgical weight loss may include post-bariatric surgery reduction of chronic inflammation and immunosuppression. 6 Therefore, this cohort study by Lazzati et al 5 is an important step toward improving the understanding of potential lifetime risks of bariatric surgery and overall major health benefits of surgically induced weight loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor Lazzati and colleagues assessed the association of bariatric surgery with esophageal and gastric cancer incidence among patients with severe obesity using retrospective cohort data. They concluded that bariatric surgery was associated with significantly lower esophageal and gastric cancer incidence and in-hospital mortality.…”
mentioning
confidence: 99%
“…In Reply We are pleased that our article provokes debate and rightly so. We are fully aware of the limitations of our work, which we detail in the article.…”
mentioning
confidence: 99%